2023
DOI: 10.1111/acps.13604
|View full text |Cite
|
Sign up to set email alerts
|

Unfavorable cancer mortality‐to‐incidence ratios in patients with schizophrenia: A nationwide cohort study in Taiwan, 2000–2019

Chu‐Syuan Cheng,
Wen‐Yin Chen,
Hu‐Ming Chang
et al.

Abstract: ObjectivesStudies on cancer incidence and mortality in patients with schizophrenia have reported inconsistent findings. In this study, we simultaneously investigated cancer incidence and mortality in patients with schizophrenia and evaluated the cancer mortality‐to‐incidence ratio (MIR), which is rare in the literature.MethodsFrom the Taiwan National Health Insurance Database, we collected the data of 107,489 patients who received a diagnosis of schizophrenia between 2000 and 2019. Data regarding cancer incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…A previous study reported a 2.9-fold higher risk of all-cause mortality in patients with schizophrenia compared to the general population, and a 1.6-fold higher risk compared to controls matched for physical diseases ( 36 ). Although several risk factors including cardiovascular diseases ( 37 ), stroke ( 37 , 38 ), smoking ( 39 ), physical fitness and inactivity ( 40 ), obesity ( 41 ), dyslipidemia ( 42 ), any cancer ( 43 ), and suicide ( 44 ) have been associated with all-cause mortality in patients with schizophrenia, the exact pathophysiological mechanisms have yet to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported a 2.9-fold higher risk of all-cause mortality in patients with schizophrenia compared to the general population, and a 1.6-fold higher risk compared to controls matched for physical diseases ( 36 ). Although several risk factors including cardiovascular diseases ( 37 ), stroke ( 37 , 38 ), smoking ( 39 ), physical fitness and inactivity ( 40 ), obesity ( 41 ), dyslipidemia ( 42 ), any cancer ( 43 ), and suicide ( 44 ) have been associated with all-cause mortality in patients with schizophrenia, the exact pathophysiological mechanisms have yet to be clarified.…”
Section: Discussionmentioning
confidence: 99%